Phonetic Characteristics of Vowels in Babbling - N, Sreedevi; S, Jyothi; N, Smitha K (Journal of All India Institute of Speech and Hearing, 2020)
Children continually fascinate adults with their incredible daily developments. One of the most impressive accomplishments is the child’s ability to produce speech sounds. In human speech, vowel is the sonority peak of a syllable and it is the most crucial element in human language. During babbling vowels exceed the number of consonants produced for most children. Vocalic development has been less extensively studied than consonant development, mainly because vocalic utterances are very difficult to transcribe reliably and thus not easy to arrive at a valid developmental profile. Therefore, recent studies on vowel development, especially in the first year, employ both perceptual transcription with high-quality recording and transcribing equipment and acoustic analysis. The purpose of the study is to examine the phonetic characteristics of vowels in 6 typically developing infants in the age range of 4 to 5 months from native Kannada speaking homes. Participant selection is based on the parent case history report. Each child is visited at home, in the fourth month of infant’s age. Audio and video recording sessions of 30 minutes for all the infants are carried out in the presence of the mother using a digital video recorder (Sony Handy cam DCR DVD 908). The recorded data are transcribed phonetically using International Phonetic Alphabet (Broad phonetic transcription method). Inter judge-reliability of phonetic transcription is evaluated by two speech language pathologists for 10% of the selected samples. The transcribed vocalizations are then analyzed for their frequency of occurrences with respect to tongue height, tongue advancement and lip rounding. The qualitative and quantitative data obtained would help to gain an insight regarding what is normally expected of an infant at the early stage of communication development and aid the Speech Language Pathologists in making appropriate clinical decisions.